CEO Turnover and Earnings Management: Can Board Gender Diversity Restraining Earnings Management? - Dwijayanti, S, Patricia Febrina; Wijaya, Hendra (Jurnal Ilmiah Akuntansi & Bisnis, 2024)
This study investigates at how CEO turnover affects earnings management. Additionally, this study examines at gender diversity as a moderator of the effect of CEO turnover on earnings management. In this study, it is expected that gender diversity will lessen agency conflicts that arise during CEO change. The study sample consists of non-financial companies that were listed on the Indonesia Stock Exchange between 2015 and 2019. The total sample in this study is 1336 observations. Earnings management measured using three measurements model namely Modified Jones, Kothari, and Rahman and Shahrur. Multiple regression analysis was used for analyzing the study’s data. This study’s findings show that the management of earnings is unaffected by CEO turnover and gender diversity has no moderating influence on the impact of CEO turnover on earnings management.